A unified approach to contract interpretation - Catterwell, Ryan (Oxford ; Hart, 2020)
"Interpretation or construction is central to the operation of contract law. Despite the fundamental role it plays, there have been limited attempts to explain construction in holistic terms. This important book aims to fill that gap by offering a systematic exposition of the iterative process. It also goes further, suggesting practical solutions to disputes regarding questions of interpretation. The book argues that construction is not simply about establishing what words mean; it is a process through which objective intention is inferred from the choice of words in a contract. The interpretive process involves four steps: formulate the question of interpretation in dispute; explore competing answers to the question; analyse the admissible material supporting each interpretation; and weigh and balance the competing considerations. By so doing, the book offers a simple yet sophisticated framework for interpreting/constructing contracts"--
Introduction -- Theories of Contract Interpretation -- The Key Features of Contract Interpretation -- A Unified Theory of Contract Interpretation -- The Cognition of Contract Interpretation : A Four-Stage Process -- The Practice of Contract Interpretation : The Resolution of Interpretive -- Disputes -- The Role of Interpretation in Contract Law -- Conclusion.
Based on author's thesis (doctoral - University of Sydney, 2017) issued under title: Construction in contract law : a logical and structured approach.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Contracts -- English-speaking countries -- Interpretation and construction; Contract law; Electronic books